Firm Closures and Labor Market Policies in Europe: Evidence from Retrospective Longitudinal Data - Nikolaos Theodoropoulos; Georgios Voucharas (Global Labor Organization (GLO), 2023)
We examine the impact of active and passive labor market policies expenditures on the probability of re-employment, re-employment duration, unemployment duration, and re-employment wages in the case of job displacements due to firm closures. We use retrospective homogeneous longitudinal data from the Survey of Health, Ageing and Retirement in Europe and OECD data for 24 countries over the period 1985-2017 and we operate within alternative econometric frameworks. Our findings suggest that, in contrast to passive labor market policies, investing in active labor market policies increases the re-employment probability and the re-employment duration, reduces the risk of staying unemployed, and leads to higher wages at the lower end of the conditional wage distribution. Passive labor market policies estimates offset active labor market estimates and their interaction effect is always negative, but complementarities effects are found for Northern countries. By breaking down active and passive labor market policies into eight subcomponents, our results indicate that they have significant heterogeneous effects within and across labor market outcomes. Further, expenditures on labor market policies vary substantially across regions. For instance, active labor market policies have a stronger impact for Eastern countries, whereas passive labor market policies such as out-of-work income has a positive impact for Southern countries. Further, females are found to benefit more from active labor market policies in terms of re-employment probability, duration of re-employment, and risk of unemployment, but not in terms of wages, compared to males. Policymakers may consider the importance of implementing diverse reforms tailored to different countries and groups to enhance the effectiveness of labor market policies.
Keywords: C21; E24; J08; J65; 330; labor market policies; plant closures; job loss; re-employment probability; unemployment duration; re-employment wages